Investigation of Vitamin D-Binding Protein Polymorphism Impact on Coronary Artery Disease and Relationship with Longevity: Own Data and a Review - Donatas Stakisaitis; Vita Lesauskaitė; Milda Girdauskaitė; Ernestas Janulionis; Albertas Ulys; Rimantas Benetis (International Journal of Endocrinology)
The aim of the study was to assess the effect of vitamin D-binding protein (DBP) polymorphism on coronary artery disease (CAD). DBP phenotypes were identified in the groups: control (n=306), men suffering from CAD (n=154), and long-lived individuals (n=108). Isoelectric focusing of DBP phenotypes in serum was performed on polyacrylamide gel. Distribution of DBP phenotypes in the study groups was found to be in Hardy-Weinberg equilibrium. Gc1s-1s phenotype and Gc1s allele frequency in CAD groups were significantly higher than in control, and Gc1s allele frequency was found significantly more often in CAD compared with long-lived group (p<0.05). The Gc2 allele frequency in control was higher as compared with Gc2 frequency in CAD group (p<0.05). The Gc2-2 phenotype was more frequent in long-lived survivors than in the CAD group (p<0.05). It was found that the Gc1s allele significantly increased the risk of CAD with the odds ratio (OR) equal to 1.45 (p<0.02) and showed Gc2 to be related with a decreased risk of CAD (OR = 0.69; p<0.03). Authors review the role of DBP in resistance to atherosclerosis and cancer as the main longevity determinants.